COMPARISON OF HYPERURICEMIA IN TYPE 2 DIABETICS ON LOW DOSE ASPIRIN AND NOT ON LOW DOSE ASPIRIN: Hyperuricemia - Malik, Maj Mahmood Iqbal (Pakistan Armed Forces Medical Journal, 2013)
Objective: To compare the frequency of hyperuricemia in type 2 diabetes patients who are taking low dose aspirin with those patients who are not taking low dose aspirin. Study design: Quasi experimental study. Place and duration of study: This study was carried out at Military Hospital Rawalpindi for a period of two years (June 2006-May 2008). Patients and Methods: Sixty diabetic patients were selected who were taking low dose aspirin comparing group A and sixty diabetic patients who were not taking aspirin were placed in group B. These patients were selected from the OPD through non probability convenience sampling. All these patients were being followed up in medical outpatient quite regularly on fort-nightly basis. Data had been collected through a carefully designed questionnaire. Results: In group A, 90% of the patients had uric acid less than 445umol/l and 10% of the patients had uric acid more than 445umol/l. whereas in group B 100% of the patients had uric acid less than 445umol/l, there was a statistically significant difference between the two groups (p< 0.05). Conclusion: Aspirin in low doses cause hyperuricemia and regular monitoring of uric acid is mandatory to prevent its adverse effects.